Sunlit, controlled‐environment chambers are essential for comparing plant responses to various climates. (3rd November 2020) - Allen, L.H.; Boote, K.J.; Jones, J.W.; Jones, P.H.; Pickering, N.B.; Baker, J.T.; Vu, J.C.V.; Gesch, R.W.; Thomas, J.M.G.; Prasad, P.V.V.
Abstract: Unique capabilities of various systems for studying the impacts of rising atmospheric CO2 concentration and other environmental factors on growth and yield of plants are presented. These systems include soil–plant–atmosphere research (SPAR) chambers, free‐air carbon dioxide enrichment (FACE) facilities, temperature‐gradient greenhouses (TGG), and open top chambers (OTC). The SPAR chambers have several advantages compared to FACE and other facilities, including: (a) constant CO2 concentration and stabile setpoints; (b) CO2 concentration controlled to any range of sub‐ambient through supra‐ambient levels, providing comparison of plant responses to past and future climates; (c) precise air and dewpoint temperature setpoints; (d) calculation of whole‐canopy photosynthesis and evapotranspiration rates at short time intervals; (e) calculation of whole‐canopy respiration rates during the night; (f) determination of plant responses to temperature alone or including other factors; (g) multiple chambers for simultaneous comparison of plant responses to varying environments, providing data for plant growth modeling; (h) low operating expense for CO2 concentration; and (i) capability of measuring N2 fixation rates in the rooting zone of legumes or methane emissions from rice ( Oryza sativa L.). SPAR systems were better suited than FACE systems for more than half of the attributes of enrichment systems identified in this paper. Limitations of plant responses due to fluctuating elevated CO2 concentration and limitations of range of elevated CO2 concentration exist for FACE systems. Controlled environments are needed for developing mathematical growth response functions under a wide range of conditions. Finally, we identified a use of portable SPAR chambers within FACE experiments for confirmation of diminished plant photosynthesis in fluctuating CO2  concentration.